Arogasi Kekuasaan dalam Qashashul Qur’an: Analisis Psikologis Tokoh Fir’aun sebagai Ibrah bagi Kepemimpinan Modern - Nurfakhruddin Al Mubarak; Nasrullah Bin Sapa; Muhammad Amin Sahib (Yayasan Al-Afif, 2025)
Power, in the Qur’anic perspective, is a divine trust (amanah) that demands both moral and spiritual accountability. Yet history reveals that power often transforms into a source of arrogance and oppression when detached from the principle of tawhid. This article explores the arrogance of power in the Qashash al-Qur’an through a psychological analysis of Pharaoh as the archetype of absolute authoritarianism. The study aims to identify the psychological dimensions of Pharaoh’s arrogance and to extract moral lessons (ibrah) relevant to contemporary leadership. Using the thematic interpretation (tafsir maudhu‘i) method with an interdisciplinary approach, it combines classical exegesis (al-Qurthubi, al-Ghazali, Ibn Taymiyyah, and al-Mawardi) with social-psychological theories of authoritarianism and power narcissism. The findings indicate that Pharaoh’s arrogance stems from spiritual blindness, delusions of self-deification, and fear of losing legitimacy. Unrestrained power leads to dehumanization and systemic injustice, while Qur’anic leadership emphasizes trust, justice, and self-purification as antidotes to tyranny. This study contributes to the interdisciplinary dialogue between Qur’anic exegesis and psychology of power, offering a normative framework for ethical, humanistic, and value-based leadership.